Postglacial organic carbon accumulation in coastal zones-A possible cause for varying atmospheric CO2 levels: preliminary data from SW Portugal - Boski, T. (2013)
We report the preliminary data on organic carbon accumulation rates which are being determined in the infill sequences of several estuaries, in the coastal fringe of Algarve (S Portugal). The so far analysed sedimentary sequences of Guadiana River estuary represent the time span from ca 10000 yr. cal BP to present. The obtained data indicate that until ca 7000 yr. cal BP, i.e. during the period of fast sea level rise, organic carbon accumulated at an average rate ranging from 160 to 320 gm yr . In the Middle and Upper Holocene, when the sea level rise was not exceeding 25cm/century the organic carbon accumulation rate dropped to an average value of ca 50 gm yr . The analysis of gas bubble content from ice cores indicates that the atmospheric CO concentration evolved during the last glacial/interglacial transition, from 180 ppv minimum during the LGM to the 270 ppmV preindustrial level. Considering that the terrestrial particulate organic matter is an essential fertiliser of the ocean, it is postulated that enhanced burial of POM in the coastal areas during the period of fast postglacial sea level rise is responsible for decrease of primary productivity in the open ocean and consequent transfer of 200 Gt. ofCto the atmosphere.